Asuhan Keperawatan Anak Dengan Bronkopneumonia Di Ruangan Anak RSUD Prof. H. Muhammad Yamin, S. H Pariaman - Suri Lidyawati; Reska Handayani; Prima Yoselina; Yessy Aprihatin (CV. ITTC INDONESIA, 2026)
Bronchopneumonia is a lung infection that generally affects the terminal bronchioles. Based on data obtained from the pediatric ward of RSUD Prof. H. Muhammad Yamin, S.H Pariaman from January 2023 to December 2025, there were 604 patients diagnosed with bronchopneumonia. The purpose of this study is for the student to be able to describe nursing care for a child (An. F) with bronchopneumonia in the pediatric ward of RSUD Prof. H. Muhammad Yamin, S.H Pariaman. The method used is a case study conducted over 5 days, from February 13 to 17, 2026, in the pediatric ward of RSUD Prof. H. Muhammad Yamin, S.H Pariaman, involving one patient (An. F) with bronchopneumonia. The process included assessment, nursing diagnosis, planning, implementation, and evaluation. After completing the assessment, four nursing diagnoses were identified: ineffective airway clearance related to retained secretions as evidenced by rhonchi, shortness of breath, and restlessness; ineffective breathing pattern related to impaired respiratory effort as evidenced by abnormal breathing patterns; hyperthermia related to the disease process as evidenced by body temperature above normal limits; and risk of nutritional deficit related to the inability to digest food. After 5 days of implementation, some nursing care problems were resolved while others remained unresolved. It is expected that parents maintain a clean and healthy lifestyle, avoid harmful habits that can trigger bronchopneumonia such as preventing children from direct exposure to cigarette smoke and avoiding direct contact with individuals who have just smoked. Additionally, providing balanced nutrition and adequate rest is important to prevent recurrent bronchopneumonia, and families are encouraged to apply the knowledge they have gained..